Analysis Factors Affect Pregnant Mother Prevention Of Mother To Child Transmission Of HIV / AIDS (PMTCT) In Balowerti Public Health Center Kediri - Rahmadina Ratri Cahyati (Journal for Quality in Public Health, 2020)
HIV / AIDS infection in mothers can cause transmission to children, especially through childbirth. Efforts to overcome to prevent transmission between mothers to babies born through prevention of mother to child transmission of HIV / AIDS (PMTCT) programs. The purpose of this study is the influence of attitudes, perceptions of control, subjective norms and husband's support for the behavior of Pregnant Women doing Prevention Of Mother Child Child Transmission Of HIV / Aids (PMTCT) in Balowerti public health center kediriThe research design used in the study was observational. The population studied was all pregnant women at the Balowerti Health Center in Kediri City, with a simple random sampling technique, a sample of 96 respondents was obtained. The independent variables studied were attitudes, perceptions of control, subjective norms and husband support, with the dependent variable pregnant women doing (PMTCT).Data analysis using the Logistic Regression test at α = 0.05 Based on the results of the Logistic Regression test showed that the attitude variable p value 0.024, perception p value 0.001, subjective norm p value 0.649 and husband support p value 0.000. So pregnant women do PMTCT are significantly influenced by attitude, perceived control, subjective norms and husband's supportPregnant women do PMTCT together influenced by attitudes, perceptions of control, subjective norms and husband support and can be influenced by other factors. A very influential factor in pregnant women to do PMTCT is positive perception of control. Because with a high positive perception, it greatly influences the motivation of pregnant women to do PMTCT to be high